2022
DOI: 10.3390/jcm11061694
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia Areata and Dexamethasone Mini-Pulse Therapy, A Prospective Cohort: Real World Evidence and Factors Related to Successful Response

Abstract: The mini-pulse oral corticosteroids treatment for alopecia areata (AA) is an accessible treatment whose efficacy and adverse effects have not yet been properly described. The objective of the study was to assess the effectiveness and safety of the mini-pulse oral corticosteroids treatment in patients with AA, and to explore potential factors associated to the response in a real-world setting. An observational study of a prospective cohort to assess the effectiveness and safety of a mini-pulse dexamethasone tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…Oral dexamethasone pulse was relatively ineffective in patients with hypothyroidism and those aged under 15 years. No greater reduction in the Severity of Alopecia Tool (SALT) score was reported in combination therapy of dexamethasone pulse and oral minoxidil (25). Another study by Sharma et al on 30 patients with widespread and diffuse AA who received oral dexamethasone showed promising results, as more than 60% of patients had completed or over 75% hair growth during five months.…”
Section: Oral Mini-pulse Of Dexamethasonementioning
confidence: 99%
“…Oral dexamethasone pulse was relatively ineffective in patients with hypothyroidism and those aged under 15 years. No greater reduction in the Severity of Alopecia Tool (SALT) score was reported in combination therapy of dexamethasone pulse and oral minoxidil (25). Another study by Sharma et al on 30 patients with widespread and diffuse AA who received oral dexamethasone showed promising results, as more than 60% of patients had completed or over 75% hair growth during five months.…”
Section: Oral Mini-pulse Of Dexamethasonementioning
confidence: 99%
“…We compared our series of patients with two other reported series in which patients received the same dosage of 0.1 mg/kg/day of dexamethasone twice weekly (Table 2). 1,10 Our data showed a higher mean age, family history, duration of AA and eyebrow and eyelash involvement. We first reported the weight of AA patients undergoing MPCT‐OD which we considered that is an important data due to the adjustment of dexamethasone dosage.…”
Section: N = 45mentioning
confidence: 99%
“…It is an oral inhibitor of JAK 1 and 2 that can interrupt the signaling of cytokines involved in the pathogenesis of alopecia areata [ 19 ]. Moreover, mini-pulse therapy with oral corticosteroids could be safer in maintaining efficacy in cases of severe alopecia areata [ 20 ].…”
Section: Introductionmentioning
confidence: 99%